1997
DOI: 10.1002/(sici)1096-8628(19971003)72:1<85::aid-ajmg18>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Patients with geleophysic dysplasia are not always geleophysic

Abstract: We report on two boys with facial anomalies, small hands and feet, joint contractures, thick skin, unusual tiptoe gait and lysosome-like inclusions in the hepatocytes, compatible with a diagnosis of geleophysic dysplasia (GD). One of them also had fibrosis and fatty degeneration of the liver. In both, the facial appearance was different and neither had short stature nor progressive cardiac valvular disease. These clinical findings, consistent with a mild form of GD, support the notion that this disorder may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Both the intra-lumenal and epithelial vesicles stained strongly with periodic acid Schiff (PAS) stain ( Fig. 3 B), consistent with the previously documented appearance of GD tracheal, liver and cardiac biopsies, which had shown carbohydrate-enriched inclusions in these organs, and led to designation of GD as a glycoprotein storage disorder ( Spranger et al, 1984 ; Shohat et al, 1990 ; Santolaya et al, 1997 ). We found that this PAS-positive material was sensitive to α-amylase digestion, indicative of substantial glycogen content ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…Both the intra-lumenal and epithelial vesicles stained strongly with periodic acid Schiff (PAS) stain ( Fig. 3 B), consistent with the previously documented appearance of GD tracheal, liver and cardiac biopsies, which had shown carbohydrate-enriched inclusions in these organs, and led to designation of GD as a glycoprotein storage disorder ( Spranger et al, 1984 ; Shohat et al, 1990 ; Santolaya et al, 1997 ). We found that this PAS-positive material was sensitive to α-amylase digestion, indicative of substantial glycogen content ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…Although the syndrome obtains its name because of the typical facies (gelios: happy, physis: nature), Santolata et al emphasised that some published cases do not have this appearance. 8 Although the underlying metabolic or genetic basis is unknown, some authors have argued that there are similarities between GD and the lysosomal storage disease, mucopolysaccharidosis, such as the coarse facial features, short stature and skeletal changes including progressive limitation of joint movement, thickened skin and microscopic changes resembling lysosome storage disorders of these tissues. 5 Conditions that might be confused with GD are: acromicric dysplasia, characterised by severe growth retardation, markedly short hands and feet and a short nose, and Moore-Federman syndrome, characterised by short limb dwarfism, stiff joints, thick skin and ocular findings such as glaucoma, cataract and retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils with abnormally coarse granulation have been reported. 8 Although most patients die in the 1st 6 years of life owing to the progressive involvement of heart valves and myocardium and, sometimes, stenosis of the upper respiratory tract, milder cases have been reported. 2,9,10 …”
Section: Discussionmentioning
confidence: 99%
“…First, thickened skin and hepatomegaly are features of both geleophysic dysplasia and Moore-Federman syndrome, but are never observed in acromicric dysplasia. Second, cardiac valve dysplasia is observed in geleophysic dysplasia only 5. Third, while life expectancy and functional prognosis are good in acromicric dysplasia and Moore-Federman syndrome, they are poor in geleophysic dysplasia 6.…”
Section: Discussionmentioning
confidence: 99%